Youth and online sports betting advertising. The Spanish experience - Fernández Rincón, Antonio Raúl (2022)
This study investigates the perception of young Spaniards about online sports betting and its advertising. The initiative arises from the recent regulation of commercial communications in this sector in Spain. We reviewed the literature related to the phenomenon and the foundations that gave rise to the regulations. Starting from discussion groups with young people between the ages of 15 and 21, we use advertisements as an impulse to learn about beliefs and perceptions about sports betting, the regulations in force and their advertising. There is a certain lack of concern in the group with the influence of advertising and the health risks of possible addictive behaviors. Studies of this type, we believe, could serve as a reference for future regulatory frameworks in the Latin American region, a territory in which this industry is in full expansion.